Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/ijefm-07-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

The role of stakeholders in shifting environmental practices of music festivals in British Columbia, Canada

Abstract: PurposeThe purpose of this paper is to increase understandings of the complexity of stakeholder relationships and their impact on environmental practices in music festivals in Western Canada, but also to highlight how managers can leverage their festival platform for stakeholders to create new partnerships that foster and support primary values around sustainability.Design/methodology/approachWe use a community-based participatory framework to guide this study, and qualitative research methods in the form of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
(156 reference statements)
0
18
0
Order By: Relevance
“…Such measures might include both voluntary and non-voluntary measures. As suggested by Hazel and Mason (2020), voluntary measures might relate to changing the residents attitudes and behavior through social marketing undertaken collaboratively by the government, non-profit organizations, and the festival organizers through promoting the benefits of behaving in environmental friendly ways that will have a trickle down effects on the festival. Non-voluntary measures that can be set by the government might include banning of littering within the festival grounds or the use of biodegradable materials for drinks and food during the festival, reducing its environmental pollution ‘footprint'.…”
Section: Discussionmentioning
confidence: 99%
“…Such measures might include both voluntary and non-voluntary measures. As suggested by Hazel and Mason (2020), voluntary measures might relate to changing the residents attitudes and behavior through social marketing undertaken collaboratively by the government, non-profit organizations, and the festival organizers through promoting the benefits of behaving in environmental friendly ways that will have a trickle down effects on the festival. Non-voluntary measures that can be set by the government might include banning of littering within the festival grounds or the use of biodegradable materials for drinks and food during the festival, reducing its environmental pollution ‘footprint'.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from Polonsky [4], the stakeholder theory has been repeatedly used by many researchers [5][6][7][8][9] in the corporate environmentalism area. As the concern for environmentalism continues to grow, managers need to understand their relationship with different stakeholder groups and the impact of these groups on their ability to incorporate environmental strategies [10]. Hence, we have proposed an extended model based on the corporate environmentalism model [8] by integrating internal and external stakeholders' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, McNamara et al (2018) found strategies rooted in softer forms of power such as attraction and inducement to be effective in mobilising resources for large-scale events. Other empirical studies show that stakeholder strategies tend to be largely collaborative (Hazel and Mason, 2020; van Niekerk, 2016; Yaghmour and Scott, 2009). In a more recent study, sports fans and participants were found to seek control of their game experience by establishing and engaging in game rituals, and by using positive or negative word-of-mouth to reward or punish management (Erhardt et al , 2019).…”
Section: Stakeholder Theory In Eventsmentioning
confidence: 99%
“…Events are dependent on external stakeholders for various resources (Getz and Andersson, 2010; McNamara et al , 2018). The event stakeholder literature suggests that different stakeholders have different hindering and facilitating potential that can influence the sustainability and survival of the event (Clarke and Jepson, 2011; Hazel and Mason, 2020; van Niekerk and Getz, 2019). In particular, the position of event external stakeholders is much harder to determine than that of internal stakeholders (van Niekerk, 2016), pointing to the importance of understanding how external stakeholders might exercise their influence in events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation